Effects of different parameters on energy - Exergy and power conversion efficiency of PV modules - Gurturk, Mert; Benli, Huseyin; Erturk, Neslihan Kocdemir (Pergamon-Elsevier Science Ltd, 2018)
Due to increase in the amount of electricity generated from solar energy, the installation of a solar energy facility based on the photovoltaic collector has accelerated. However, work-life of these power plants is planned for 25 years. In this 25 years period, there are many parameters that can affect the PV collector efficiency. The authors of this study observed many solar power plants and some of these parameters were determined. Many researchers investigated the effect of the wind load, load test and dust on the surface of the collectors. However, authors of this study investigated cleaning process and dust damage effect carried by the wind. Examples used in the experimental were evaluated according to a concept which is before and after. Before, measurements of current, voltage, power and energy-exergy, power conversion efficiencies of the example, which is the PV module, had determined and all these values were determined again after applying parameters which are cleaning process and dust damage effect carried by the wind. Results show that serious decrease in efficiency parameters is obtained. Energy, exergy and power conversion efficiency of the PV module are determined as 2.19%, 1.46% and 1.44% for after the wind-dust test, respectively. The maximum decrease in energy, exergy and power conversion efficiencies occur 17.87%, 19.37% and 19.62% due to using a squeegee for the cleaning process, respectively.
Keywords: Photovoltaics; Energy efficiency; Exergy; Power conversion, solar power plant; Renewable energy